2021
DOI: 10.5373/jardcs/v12i6/20202652
|View full text |Cite
|
Sign up to set email alerts
|

Application of Technology Acceptance Model (TAM) in Consumer Behavioral Intention towards Online Shopping

Abstract: Online shopping isasasas buying products or services via the internet using a computer or mobile platform. It provides a different policy and environment to both consumers and suppliers for having business activities in a digital environment than a traditional way. Some countries are highly adopted and utilizing online shopping for their day to day operations. There are some differences among countries in consumers’ buying behavior toward online shopping, which may be the reason for comfortability and reliabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Chen and Li (2020) investigated college students' online travel booking behavior and found that perceived usefulness has a significant positive impact on users' use attitudes and adoption intentions. In addition, Kariapper (2020) found that perceived usefulness significantly affected online booking attitudes. It follows that when an online mobile application can better help an individual complete a booking task, he or she will develop a more positive attitude, which will lead to higher adoption intention.…”
Section: A Metaanalysis Of Otbs Adoptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chen and Li (2020) investigated college students' online travel booking behavior and found that perceived usefulness has a significant positive impact on users' use attitudes and adoption intentions. In addition, Kariapper (2020) found that perceived usefulness significantly affected online booking attitudes. It follows that when an online mobile application can better help an individual complete a booking task, he or she will develop a more positive attitude, which will lead to higher adoption intention.…”
Section: A Metaanalysis Of Otbs Adoptionmentioning
confidence: 99%
“…The easier the online booking procedure is to use and operate, the higher the perceived usefulness and the stronger the intention to book online (Mohamad et al, 2021). In addition, it has been demonstrated that there is a significant relationship between perceived ease of use and attitude (Kariapper, 2020). If individuals perceive the ease of using OTBS, they will have a positive attitude toward it.…”
Section: Perceived Ease Of Usementioning
confidence: 99%
“…People shop online for various reasons, the most important of which is the convenience of not having to travel to a physical store to make a purchase, the option to compare prices across numerous websites at once, the chance to escape traffic, the opportunity to save time and fuel cost (Al-Dwairi & Kamala, 2009 ). Earlier research found evidence that people’s socioeconomic status significantly impacts online shopping (Kariapper, 2021; Nawi et al, 2019; Shawon et al, 2018; Uddin & Sultana, 2015). For instance, Uddin and Sultana (2015) noted that the more money and education people have, the more they make online purchasing.…”
Section: Introductionmentioning
confidence: 99%
“…A study published in 2020 in India concluded that the essential factors in choosing an online pharmacy were quick service, doorstep delivery, and reduced cost of medicine, while privacy, accessible payment mode, and decreased error rate were also mentioned [14]. Knowledge, age, income, attitude toward the online media, residence, and other factors influence the level of adoption of this pharmacy channel [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacies are also considering opportunities given by the online media due to easy access to advertising activities towards lucrative segments of the population, the ability to convey customized messages using web-based tools, and a way to capitalize on competitive operational advantages, such as low prices or quick delivery [6,7,16].…”
Section: Introductionmentioning
confidence: 99%